2001
DOI: 10.1046/j.1365-2273.2001.00398.x
|View full text |Cite
|
Sign up to set email alerts
|

The sense of coherence: a tool for evaluating patients with peripheral vestibular disorders

Abstract: Peripheral vestibular disorders may result in physical as well as psychosocial dysfunction. Such a situation demands a capacity to cope which lately has been discussed as an important factor in the health outcome. Antonovsky has described the concept of sense of coherence (SOC) as such a trait and has developed a questionnaire (the SOC Scale) to measure it. The aim of this study was to describe the patients' self-rated degree of SOC and to set this in relation to their perception of the self-rated quality of l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
2

Year Published

2002
2002
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 24 publications
0
25
2
Order By: Relevance
“…Furthermore, they demonstrated less dizziness-specific anxiety at the onset of the vestibular disease. Mendel et al [29] were the first to examine the relationship between peripheral vestibular disorders and the sense of coherence (SOC). They showed that high SOC scores were significantly correlated with lower handicap scores, psychosocial dysfunction, and mental comorbidity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, they demonstrated less dizziness-specific anxiety at the onset of the vestibular disease. Mendel et al [29] were the first to examine the relationship between peripheral vestibular disorders and the sense of coherence (SOC). They showed that high SOC scores were significantly correlated with lower handicap scores, psychosocial dysfunction, and mental comorbidity.…”
Section: Discussionmentioning
confidence: 99%
“…They showed that high SOC scores were significantly correlated with lower handicap scores, psychosocial dysfunction, and mental comorbidity. SOC was postulated as an important predictor for dizziness-specific quality of life [29]. In a representative German study, patients without lifetime mental disorders reached higher scores on SOC [24].…”
Section: Discussionmentioning
confidence: 99%
“…614 cessful coping with stressful situations and characterizes good adaptation to the disease and its treatment. 34,35 A patient who understands the necessity of strict adherence manages to take the medication successfully and finds meaning in doing so is more likely to have a high SOC, in other words to deal effectively with the situation.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies indicate that patients with HIV infection have lower SOC than samples from the general population and lower than patients suffering from less chronic diseases. [33][34][35] The diagnosis of HIV and the circumstances that are required regarding treatment with antiretroviral therapy is a complex and probably stressful situation to live with. 33 Adherence to antiretroviral treatment in connection with how well HIV-infected patients cope and adapt to the disease has not, as far as we know, been studied before.…”
Section: Introductionmentioning
confidence: 99%
“…Regardless of the method by which the positive experience is gained, the results indicate that meaningfulness of the behaviour has a curative effect on Menière's disorder. In patients with peripheral vestibular lesions, the higher scores in the SOC correlated very significantly with lower scores in the Vertigo Handicap Questionnaire (24). Yardley et al (22) also pointed out that attitudes of health professionals and society towards providing help was important.…”
Section: Duration Of Symptomsmentioning
confidence: 98%